History versus customary law: Commission on Traditional Leadership: Disputes and Claims - Peires, Jeff (SA crime quarterly, 2016)
This article examines the practices of the Commission on Traditional Leadership: Disputes and Claims, set up under the Framework Act of 2003 to ‘cleanse’ the institution of traditional leadership by ridding it of the illegitimate traditional leaders installed during the colonial and homeland eras. Close analysis of the Commission’s hearings and determinations with regard to kingship claims by the Western Mpondo and Mpumalanga Ndebele shows that the Commission violated not only the historical past but even the limited constraints of binding legislation, in order to impose its own preferences in the name of custom. The experience of the Commission therefore highlights one of the most fundamental deficiencies in the Framework Act, namely insisting on the guiding role of ‘custom’ while failing to define the meaning of the term and its implications.